Assessment of induced delamination drilling of natural fiber reinforced composites: a statistical analysis - Benyettou, Riyadh; Amroune, Salah; Slamani, Mohamed; Seki, Yasemin; Dufresne, Alain; Jawaid, Mohammad; Alamery, Salman (Elsevier, 2022)
This work focuses on the study of the drilling performance of bio composites reinforced with date palm fibers (CDPF). It is a new fiber that is characterized in terms of piercing behavior for the first time. The experimental study was carried out with three types of drills, with a diameter of 10 mm and feed and spindle speeds of the order of (40, 80 and 200 mm/min) and (560, 1120 and 2240 rpm), respectively. The drilling performance was assessed in terms of delamination and surface quality, such as circularity and cylindricity of the drilled holes. Using the CMM machine, the value of the delamination factor was determined using Image J software. The results showed that the value of the latter increased with the increase in feed rate and decreased with the increase in spindle speed. The delamination factor has maximum and minimum values of approximately 1.98 and 1.01 respectively. For the first time, RSM and ANOVA were used to assess the influence and interaction of input parameters (cutting conditions) on the output parameters (delamination factor Fd) during drilling of CDPF. The results obtained help manufacturers, to choose the most appropriate machining conditions to achieve better machinability for other newly developed NFRCs in the aeronautical and defense industry where the substitution of the synthetic fibers by the natural fibers becomes inevitable for economic reasons.